1998
DOI: 10.1046/j.1365-2958.1998.00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Internalin B is essential for adhesion and mediates the invasion of Listeria monocytogenes into human endothelial cells

Abstract: SummaryListeria monocytogenes causes rhombencephalitis in humans and animals and also affects the fetus in utero, causing disseminated sepsis. In both instances, the infection occurs by the crossing of endothelial cells lining a physiological barrier, the blood-brain barrier or the transplacental barrier. In this study, the ability of L. monocytogenes wild-type EGD to invade human umbilical vein endothelial cells (HUVECs) was evaluated using wild-type bacteria and isogenic Listeria mutants. Here, we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 160 publications
(108 citation statements)
references
References 43 publications
(60 reference statements)
5
99
0
4
Order By: Relevance
“…The region from amino acid residues 184 -200 showed homology to leucine-rich repeats of internalin B protein of Listeria monocytogenes. The leucine-rich repeats of internalin B has been shown to be required for inducing phagocytosis in non-phagocytic cells such as hepatocytes and endothelial and epithelial cells (46,47). We reported that FTL_0325 suppresses proinflammatory cytokines primarily by interfering with NF-B signaling (37).…”
Section: Discussionmentioning
confidence: 92%
“…The region from amino acid residues 184 -200 showed homology to leucine-rich repeats of internalin B protein of Listeria monocytogenes. The leucine-rich repeats of internalin B has been shown to be required for inducing phagocytosis in non-phagocytic cells such as hepatocytes and endothelial and epithelial cells (46,47). We reported that FTL_0325 suppresses proinflammatory cytokines primarily by interfering with NF-B signaling (37).…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, nucleotide-nucleotide BLAST searches were conducted to compare the gene sequences of L. monocytogenes transcriptional regulators against the genome sequence of L. innocua (Glaser et al, 2001); three genes (lmo2672, lmo1116 and lmo1134), which had the lowest nucleotide identity with any sequences from the L. innocua genome, were selected from the published L. monocytogenes EGD-e transcriptional regulator list. In addition, as internalins play important roles in listerial internalization and virulence (Gaillard et al, 1991;Lingnau et al, 1995;Parida et al, 1998), we selected two genes (lmo2470 and lmo2821) that encode internalin-like proteins from the L. monocytogenes EGD-e genome sequence, which do not have orthologues in the L. innocua genome (Glaser et al, 2001). (Erdenlig et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Detection of InlA and InlB on parental and L-form cells was performed using polyclonal antibodies raised against InlA and InlB (Parida et al, 1998; kindly provided by Sabine Pilgrim, University of Wuerzburg, Germany). On a piece of parafilm (Pechiney Plastic Packaging Company, USA), a drop of the respective cell suspensions was covered with a round cover slip to let the cells adhere.…”
Section: Immunolabelling Of Cell Wall and Membrane-anchored Proteinsmentioning
confidence: 99%